Increase in muscle endurance in mice by dietary Yamabushitake mushroom (Hericium erinaceus) possibly via activation of PPARδ. (1st April 2019) - Komiya, Yusuke; Nakamura, Toshiya; Ishii, Momoko; Shimizu, Kuniyoshi; Hiraki, Eri; Kawabata, Fuminori; Nakamura, Mako; Tatsumi, Ryuichi; Ikeuchi, Yoshihide; Mizunoya, Wataru
Abstract: Skeletal muscle fiber is largely classified into two types: type 1 (slow‐twitch) and type 2 (fast‐twitch) fibers. Meat quality and composition of fiber types are thought to be closely related. Previous research showed that overexpression of constitutively active peroxisome proliferator‐activated receptor (PPAR)δ, a nuclear receptor present in skeletal muscle, increased type 1 fibers in mice. In this study, we found that hexane extracts of Yamabushitake mushroom ( Hericium erinaceus ) showed PPARδ agonistic activity in vitro . Eight‐week‐old C57BL/6J mice were fed a diet supplemented with 5% (w/w) freeze‐dried Yamabushitake mushroom for 24 hr. After the treatment period, the extensor digitorum longus (EDL) muscles were excised. The Yamabushitake‐supplemented diet up‐regulated the PPARδ target genes Pdk4 and Ucp3 in mouse skeletal muscles in vivo . Furthermore, feeding the Yamabushitake‐supplemented diet to mice for 8 weeks resulted in a significant increase in muscle endurance. These results indicate that Yamabushitake mushroom contains PPARδ agonistic ligands and that dietary intake of Yamabushitake mushroom could activate PPARδ in skeletal muscle of mice. Unexpectedly, we observed no significant alterations in composition of muscle fiber types between the mice fed control and Yamabushitake‐supplemented diets.